Active inductor based fully integrated CMOS transmit/ receive switch for 2.4 GHz RF transceiver - Bhuiyan,Mohammad A.S. (2016)
Modern Radio Frequency (RF) transceivers cannot be imagined without high-performance (Transmit/Receive) T/R switch. Available T/R switches suffer mainly due to the lack of good trade-off among the performance parameters, where high isolation and low insertion loss are very essential. In this study, a T/R switch with high isolation and low insertion loss performance has been designed by using Silterra 0.13µm CMOS process for 2.4GHz ISM band RF transceivers. Transistor aspect ratio optimization, proper gate bias resistance, resistive body floating and active inductor-based parallel resonance techniques have been implemented to achieve better trade-off. The proposed T/R switch exhibits 0.85dB insertion loss and 45.17dB isolation in both transmit and receive modes. Moreover, it shows very competitive values of power handling capability (P1dB) and linearity (IIP3) which are 11.35dBm and 19.60dBm, respectively. Due to avoiding bulky inductor and capacitor, the proposed active inductor-based T/R switch became highly compact occupying only 0.003mm2 of silicon space; which will further trim down the total cost of the transceiver. Therefore, the proposed active inductor-based T/R switch in 0.13µm CMOS process will be highly useful for the electronic industries where low-power, high-performance and compactness of devices are the crucial concerns.